Impacto del proyecto educativo de la I.E.P. gratuita “Corporación de Educación Popular” en Ramón Castilla, distrito de Huanchaco, 2020 - Cabrera Calderón, Rossella Isabel (2023)
The purpose of this research is to determine the impact of the Educational Project of the free Private Educational Institution "Corporación de Educación Popular" in Ramón Castilla, district of Huanchaco, a non-experimental study was carried out and the quantitative method was applied, in the descriptive modality, with a sample of 60 parents, 8 teachers and 3 members of the management committee, men and women, randomly selected. The survey technique and its instrument called Likert-type scale questionnaire were used. The results show that the impact of the Educational Project of the free I.E.P. "Corporación de Educación Popular" is high. Chapter I describes the problematic reality, the justification of the research, the theoretical bases on the Educational Project, the general objective and the specific objectives. Chapter II develops the object of study, the research design, the population, the sample, the instrumentation, the methods and the techniques used. Chapter III shows the results and examines the surveys applied to the sample. Chapter IV discusses the results and interprets the findings. Finally, Chapters V, VI and VII present the conclusions, recommendations and bibliographical references, respectively.